Smart grid : networking, data management, and business models - Mouftah, Hussein T.; Erol-Kantarci, Melike (Boca Raton : CRC Press, Taylor & Francis Group, CRC Press is an imprint of the Taylor & Francis Group, an informa Business, 2016)
"The electric grid, empowered by intelligence, is transforming our society in many aspects, including communities that share power and smart homes that save energy. The traditional components of the electric grid, i.e., generation, transmission, distribution and consumption are evolving with innovations coming from different backgrounds. This book offers a clear presentation of networking, data management and business models in the smart grid plus a thorough understanding of cutting-edge topics such as microgrids, electric vehicles, grid analytics and dynamic pricing."--
Includes bibliographical references.
1 2
Keywords: Smart power grids; Smart power grids